(untitled) (Global Journal of Human-Social Science, 2017)
This research is to evaluate the performance of community Development programmes and poverty alleviation among the rural dwellers in Oluyole and Ibadan North East Local Government Areas of Oyo state The study is aimed to assess the high rate of Community Development and poverty alleviation in some selected communities The work was carried out in this local government and random sample techniques were used to select respondents in this study The sample size used was 600 which gave 40 of the population to be sampled from each of the community Primary and Secondary data were used for the study Six hundred and ten 610 questionnaires were personally administered to the respondents randomly selected from the six communities within the Local Government The data collected was coded and processed into computer and spss software package was used to analysis the data collected The tools of analysis were frequency distribution percentage and Chi-Square analysis 60 of the respondents sampled where male while 40 were female 46 0 with frequency of 276 were Christian 12 0 of the people sampled had primary education 8 0 had secondary education 38 0 tertiary education and 8 0 indicated no formal education while 14 indicate others 28 0 of the population was single 40 were married and 20 0 were separated while 12 0 were widow er Highest level of income was observed in 22 of the respondent that received 30 000 and above per annum Development Programmes such as NAPEP NDE FADU among others which has help young school leavers and graduates to benefit to different Agricultural Programmes in Oyo State and Nigeria at large The benefit of Community Development Programme on poverty alleviation has help in improving the life of rural dwellers in Oluyole and Ibadan North East Local of Oyo state and also in Nigeria in general by putting food on their table and labour employment to populace